An intelligent and improved density and distance-based clustering approach for industrial survey data classification. (February 2017) - Zhong, Jingjing; Tse, Peter W.; Wei, Yiheng
Highlights: An intelligent and automatic process to rank the performance in asset management. An intelligent system to automatically find the most suitable practice for benchmarking. An improved approach to determine the center of clusters. Define outlier factors and analysis so that the best and poorest performers can be identified. Abstract: Engineering Asset Management (EAM) emphasizes on achieving sustainable business outcomes and competitive advantages by applying systematic and risk-based processes to decisions concerning an organization's physical assets. Nowadays, there is no specific method to evaluate performance of EAM and lack of benchmark to rank performance. To fill this gap, an improved density and distance-based clustering approach is proposed. The proposed approach is intelligent and efficient. It has largely simplified the current evaluating method so that the commitment in resources for manual data analyzing and performance ranking can be significantly reduced. Moreover, the proposed approach provides a basis on benchmarking for measuring and ranking the performance in Engineering Asset Management (EAM). Additionally, by using the intelligent approach, companies can avoid to pay expensive consultant fees for inviting external consultancy company to provide the necessary EAM auditing and performance benchmarking.